Monday

December 22, 2014

December 22, 2014

Posted by **Jennifer** on Tuesday, March 31, 2009 at 1:20pm.

3y^2 + 4y - 2 ≥ 0

3y^2 + 4y - 2 = 0

y = [-4 ± sqrt (4^2 - 4(3)(-2)]/(2 • 3) = (-4 ± sqrt 40)/6 = (-4 ± 2 rad 10)/6 = (-2 ± rad 10)/3

Is this right?

- Pre Cal. -
**Reiny**, Tuesday, March 31, 2009 at 1:41pmyou have solved the "equation" but you were dealing with an inequation.

the values of (-2 ± √10)/3 are the intercepts on a y-number line.

so the solution would be

y ≤ (-2 - √10)/3 OR y ≥ (-2 + √10)/3

too bad it did not factor, it would have been easier to see.

**Answer this Question**

**Related Questions**

Mathforme - 5. 4x + 2 = x + 8. (1 point) x = 4 x = 3 x = 2 x = 1 Solve the ...

kbMath - 5. 4x + 2 = x + 8. (1 point) x = 4 x = 3 x = 2 x = 1 Solve the ...

7th grade math help Ms. Sue - 3. Which of the following equations has an ...

Math - Solve the linear programming problem by the method of corners. Minimize C...

7th grade math Ms. Sue please - 1. 5h – 9 = –16 + 6h (1 point) 4 –7 7 10 2. 4x...

ALGEBRA - 2nd posting - my mistake When will the dependent variable in the ...

ALGEBRA - When will the dependent variable in the equation Y=[(sqrt)(x+4-3)] ...

Algebra--Correction? - Solve x^2 -3x is greater than or equal to 10 Would the ...

Algebra - When will the dependent variable in the equation Y=[(sqrt)(x+4-3)] ...

algebra 1 - the french club is sponsering a bake sale. they spent $77 in ...